Loss of Wiz Function Affects Methylation Pattern in Palate Development and Leads to Cleft Palate - Bukova, Ivana; Szczerkowska, Katarzyna Izabela; Prochazkova, Michaela; Beck, Inken M.; Prochazka, Jan; Sedlacek, Radislav (Frontiers in Cell and Developmental Biology, 2021)
WIZ (widely-interspaced zinc finger) is associated with the G9a-GLP protein complex, a key H3K9 methyltransferase suggesting a role in transcriptional repression. However, its role in embryonic development is poorly described. In order to assess the loss of function of WIZ, we generated CRISPR/Cas9 WIZ knockout mouse model with 32 nucleotide deletion. Observing the lethality status, we identified the WIZ knockouts to be subviable during embryonic development and nonviable after birth. Morphology of developing embryo was analyzed at E14.5 and E18.5 and our findings were supported by microCT scans. Wiz KO showed improper development in multiple aspects, specifically in the craniofacial area. In particular, shorter snout, cleft palate and cleft eyelids were present in mutant embryos. Palatal shelves were hypomorphic and though elevated to a horizontal position on top of the tongue, they failed to make contact and fuse. By comparison of proliferation pattern and histone methylation in developing palatal shelves we brought new evidence of importance WIZ dependent G9a-GLP methylation complex in craniofacial development, especially in palate shelf fusion.